Adaptive buffer control for distributed autonomous robust routing in mobile surveillance robots. (April 2015) - Kim, Joongheon; Hong, Song-Nam
Abstract: This paper proposes a distributed and autonomous routing algorithm for distributed mobile surveillance robotics platforms using 60 GHz wireless technologies. According to the fact that 60 GHz wireless signals are too weak to survive in long-distance or non-line-of-sight situations due to high attenuation, advanced communication algorithms are required including beamforming, beam training, and multi-hop routing. For multi-hop robust distributed routing, each robotics platform computes the amounts of power allocation for transmitting packets from its own buffer. The amount of power allocation is determined by solving joint stochastic optimization of (i) the minimization of the summation of time average expected power consumption and (ii) the buffer stability in each unit time slot. The performance of the proposed algorithm is evaluated and it is observed that the proposed algorithm achieves desired performance.